Synthesis of pH Sensitive Hydrogels Based on Poly Vinyl Alcoholand Poly Acrylic Acid: Synthesis of pH sensitive hydrogels5 - Zahra Fahimi,; Maryam Parviz,; Fariba Orang,; Shahin Bonakdar, (Iranian Journal of Pharmaceutical Sciences, 2008)
In this research, hydrogels based on poly vinyl alcohol and poly acrylic acid blend were prepared which were cross-linked by applied thermal conditions. Afterward,effects of time and heating on water uptake were investigated. The highest wateruptake value exhibited by the sample that was heated for 20 min. at 110 ºC was about 2129% after 4 days at equilibrium state. Hydrogels exhibited pH-sensitive behaviors in a way that decreasing pH values down to 4.8 did not have any effect on the hydrogels size, whereas with increasing pH upto 8, the hydrogels were expanded.These synthetic hydrogels were evaluated as a controlled drug delivery systems and theophylline released concentration was measured by UV-spectrophotometeric method at different pH values.In vitrobiocompatibility experiments were undertaken using L-929 mouse fibroblast cell lines where the results showed appropriate cellattachment and cell spreading with spindle like morphologies.